Pendampingan Pembelajaran melalui Program KKN untuk Meningkatkan Keterlibatan Belajar Siswa Sekolah Dasar di Desa Bendungan - Aniwati Rahayu; Laila Suci Rahmadhania; Nazila Echa Ayudia; Priyadita Dewi Nanggraeni; Diyo Prabowo; Naylul Azmil Mubarok; Diah Novita Fardani (CV. ITTC INDONESIA, 2026)
Limited instructional time, combined with low levels of student engagement and self-confidence among students at SD Bendungan, necessitated an intervention in the form of participatory learning support. This community service initiative aimed to foster active engagement and cultivate positive character traits among students through the UIN Raden Mas Said Surakarta Student Community Service (KKN) program. An interactive learning support method was employed, comprising stages of needs assessment, planning, implementation, and evaluation. Data were collected qualitatively through observation, interviews, and documentation. The results indicate that integrating Student Orientation Period (MPLS) support, anti-bullying education, and creative photobooth decoration activities successfully boosted students' confidence in expressing opinions, learning enthusiasm, understanding of anti-bullying concepts, and collaborative skills. The program proved vital in creating a safe, enjoyable, and participatory school environment, serving as an effective solution for strengthening character education in primary schools.